In silico analysis of anti-dengue activity of faloak (Sterculia quadrifida R. Br) stem bark compounds - Audrey G. Riwu; Jusak Nugraha; Djoko A. Purwanto; Erwin A. Triyono (GarVal Editorial Ltda., 2022)
Context: Dengue is one of the most common infectious diseases found in tropical and subtropical regions, particularly in urban and semi-urban areas. Management dengue until now has not had a specific therapy. The development of dengue therapy using traditional plants as the main source of dengue therapy is needed. Sterculia quadrifida R. Br stem bark is one of the traditional plants in Indonesia, widely used by local people to treat various diseases. Aims: To identify the potency of S. quadrifida stem bark extract against the envelope protein and NS5 RdRp (RNA-dependent RNA polymerase) in dengue infection through in silico approach. Methods: All ligands from S. quadrifida stem bark extract from the previous study and protein preparations were retrieved from the PubChem and RSCB data bank database, respectively. Drug-likeness using Lipinski's rule of five methods. Pyrx, PyMOL, and Discovery Studio 2.0 were used to analyze and visualize the potency of S. quadrifida stem bark-specific compounds against the envelope and NS5 RdRp. Results: Epicatechin and scopoletin have the lowest affinity bond, some noncovalent interaction, and also similarity in the position of the amino acid interaction to the reference control ribavirin. Conclusions: Epicatechin and scopoletin from S. quadrifida have antiviral potential against dengue by disposing of envelope protein and NS5 RdRp.